What Determines Income Enhancement In The Creative Economy Sector? - Satya Kristi Aprilianto; Jihad Lukis Panjawa; Lorentino Togar Laut (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The growth of the Creative Economy has become a crucial driver of economic development. In Indonesia, the potential for growth in the creative economy surpasses that of the tourism industry. This research is dedicated to examining the factors that influence the earnings of creative economy entrepreneurs in Magelang Regency. The method of analysis employed is multiple linear regression. The findings reveal that labour and capital play a substantial role in determining the income of creative economy entrepreneurs. Conversely, factors such as business longevity, education, and skills do not significantly impact the income of creative economy entrepreneurs. Entrepreneurs in the creative economy must prioritize effective labour management and invest in the development of human resources, as labour has been proven to be a key determinant of income. Implementing appropriate recruitment strategies and fostering a productive team environment are essential for success in this sector